The macroeconomic impact of transportation investment on the Spanish economy - Cosculluela-Martínez, Carolina; Flores de Frutos, R. (European Journal of Transport and Infrastructure Research, 2015)
This paper compares the responses of employment and GDP Spanish growth to a permanent unitary shock in different types of transport capital stock, with those estimated in the literature. The theoretical model used to estimate the step response functions is the multiple equations dynamic model proposed by Flores et al.. (1998) adapted to this particular problem. Results suggest that: (1) The standard single equation static methodology underestimates the elasticity of the capital stock with respect to output, due to the existence of feedback relationships among transport capital stock and output. (2) The exclusion of the remaining net capital stock from the model, when dealing with a particular type of transport capital stock, might lead to biases in the estimation of the responses.